2014
DOI: 10.1021/bm500662z
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hydrogel–Solution System of Silk with High Beta-Sheet Content

Abstract: Silkworm silk has been widely used as a textile fiber, as biomaterials and in optically functional materials due to its extraordinary properties. The β-sheet-rich natural nanofiber units of about 10–50 nm in diameter are often considered the origin of these properties, yet it remains unclear how silk self-assembles into these hierarchical structures. A new system composed of β-sheet-rich silk nanofibers about 10–20 nm in diameter is reported here, where these nanofibers formed into “flowing hydrogels” at 0.5–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
214
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(222 citation statements)
references
References 51 publications
6
214
2
Order By: Relevance
“…All natural spider and silkworm silks appear to display a nanofibrillar substructure, and there is ample evidence that these fibrils contribute significantly to the prodigious mechanical properties of silks. 64,65 Assembly of RSF into fibrils with native-like structure has been demonstrated; 34,[38][39][40][41]43,44,54,57 however, while such fibrillar artificial silks are relatively robust compared to other biological materials and promise a novel range of properties in composite applications, 38,44 their mechanical properties still fall short of their natural silk counterparts. 9,38,40,43,44,54,57 The diminished capability of RSF to self-assemble is in line with past studies that have revealed deviations in the structure and bonding character of the RSF molecule.…”
Section: ■ Discussionmentioning
confidence: 99%
“…All natural spider and silkworm silks appear to display a nanofibrillar substructure, and there is ample evidence that these fibrils contribute significantly to the prodigious mechanical properties of silks. 64,65 Assembly of RSF into fibrils with native-like structure has been demonstrated; 34,[38][39][40][41]43,44,54,57 however, while such fibrillar artificial silks are relatively robust compared to other biological materials and promise a novel range of properties in composite applications, 38,44 their mechanical properties still fall short of their natural silk counterparts. 9,38,40,43,44,54,57 The diminished capability of RSF to self-assemble is in line with past studies that have revealed deviations in the structure and bonding character of the RSF molecule.…”
Section: ■ Discussionmentioning
confidence: 99%
“…2830 Silks were boiled in 0.02 M aqueous Na 2 CO 3 solution for 20 min, and then rinsed thoroughly with distilled water to extract the residual sericin. The extracted silk was placed in 9.3 M LiBr solution at 60°C for 4 h to achieve a 20% (w/v) solution.…”
Section: Methodsmentioning
confidence: 99%
“…36 The hydrogels were composed of silk nanofibers with beta-sheet content as the dominant conformation and their gel state was depended on silk concentration (Fig. 1).…”
Section: Formation Of Dox-loaded Nanofiber Silk Hydrogelsmentioning
confidence: 99%
“…1C), as in our previous study. 36 Large amplitude oscillatory rheology revealed the thixotropic properties of the silk nanofiber hydrogels. In a wide strain sweep, the G' of the hydrogels decreased rapidly following increased strain, suggesting a collapse of the gels to a quasi-liquid ( Fig.…”
Section: Formation Of Dox-loaded Nanofiber Silk Hydrogelsmentioning
confidence: 99%